Study of Nickel Leaching Using Sulfuric Acid and Phosphoric Acid on The Selectivity Nickel Ore - Syamsul Hidayat; Sri Yulianti; Dian Anggreini; Syamsul Bahtiar (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
Study of nickel leaching using sulfuric acid and phosphoric acid on the selectivity of low-grade laterite nickel ore under atmospheric conditions has been successfully carried out. In this study, the laterite nickel leaching process was carried out by varying the solution concentration and operating time. The concentrations of sulfuric acid and phosphoric acid solutions were varied at 5 M and 6 M concentrations, while the operating time was varied at 4 hours and 6 hours. For other operating conditions, it is kept constant with an operating temperature of 90 Ã¢âÆ, pulp density 15% w / v, particle size Ã¢â°Â¤ 200 mesh. After that, the analysis stage was carried out using an atomic absorption spectroscopy (AAS) tool to determine the nickel content in the sample. The results showed that the highest nickel recovery was obtained at the concentration of 5 M sulfuric acid solution of 2.60% and 5 M phosphoric acid of 2.59% with the optimum operating time at 4 hours of operating time.